Educating for a sustainable future? : perceptions of bioeconomy among forestry students in Sweden - Bernö, Hanna (SLU/Dept. of Forest Economics, 2019)
Unsustainable consumption has led to the crossing of several planetary boundaries, which is threatening life on this planet as we know it. To be able to cope with this challenge, CE, Circular Economy, has been introduced as a way forward. Additionally, often seen as a subcategory of CE, bioeconomy is a frequently used word in the sustainability debate. It is a concept associated with using renewable, bio-based resources. However, scientists still stand without a common definition of the concept.